Mediastinal extension of amoebic liver abscess: A case report on the rare thoracic complication of Entamoeba histolytica - Gautam Jesrani; Jaspreet Kaur; Samiksha Gupta; Yuvraj Singh Cheema; Prashant Ahlawat (Turkish Journal of Emergency Medicine)
Amoebic liver abscess is one frequently encountered intra-abdominal infection, caused by Entamoeba histolytica and has various abdominal and thoracic life-threatening complications. Herein, describe a case of a 30-year-old female, who suffered from multiple amoebic liver abscesses and presented with massive right-sided pleural effusion. She was managed with recommended antibiotics and pigtail catheter for liver abscess and an intercostal drainage tube for massive pleural effusion. However, postintercostal drainage, her chest X-ray demonstrated a right mediastinal shadow, which was confirmed as an intrathoracic extension of the hepatic liver abscess on computed tomography. An ultrasound-guided pigtail catheter was manipulated and placed at the site of thoracic communication. This led to clinical and radiological improvement, but unfortunately, she developed ventilator-acquired pneumonia and died due to her illness. The case represents an uncommon complication of amoebic liver abscess, which is rarely described and adds more knowledge on the thoracic complexities of this infectious disease.